84.2k views
5 votes
Which expression is equivalent to 3x^-6y^-3/15x^2y^10 ? Assume x=0 and y=0

Which expression is equivalent to 3x^-6y^-3/15x^2y^10 ? Assume x=0 and y=0-example-1
User Okuhle
by
5.3k points

2 Answers

4 votes

\bf ~~~~~~~~~~~~\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------\\\\ \cfrac{3x^(-6)y^(-3)}{15x^2y^(10)}\implies \cfrac{3}{15}\cdot \cfrac{x^(-6)y^(-3)}{x^2y^(10)}\implies \cfrac{1}{5}\cdot \cfrac{1}{x^2x^6y^(10)y^3} \\\\\\ \cfrac{1}{5}\cdot \cfrac{1}{x^(2+6)y^(10+3)}\implies \cfrac{1}{5x^8y^(13)}
User Cmaluenda
by
4.9k points
4 votes
Find the attachment below
Which expression is equivalent to 3x^-6y^-3/15x^2y^10 ? Assume x=0 and y=0-example-1
User Ricafeal
by
5.6k points